Legal consequences, measures of prevention and reduction of medical malpractice cases (errors) - Запорожченко, Анастасія Олексіївна; Запорожченко, А. О.; Запорожченко, Анастасия Алексеевна; Zaporozhchenko, Anastasiia О.; Янчук, Артем Олександрович; Янчук, А. О.; Янчук, Артем Александрович; Yanchuk, Artem O.; Катеринчук, Іван Петрович; Катеринчук, І. П.; Катеринчук, Иван Петрович; Katerynchuk, Ivan P.; et al. (Zaporozhye State medical university, 2019)
This work is purposed for determining grounds for legal consequences to come when any medical malpractice cases occur. Aim. The goal of our research is to determine the quintessence features of “medical malpractice (error)” in the medical-legal context so to determine legal consequences of medical malpractices (errors), and to classify the regulatory measures of prevention of medical malpractice cases and reduction of these problems. Methods: Semiotical, synergetic, anthropological and hermeneutical, method of normative comparison. Results. Detecting the current medical malpractice (medical error) becomes more complicated due to its definition as highly significant differences in interpreting, understanding, qualifying, finding defects, medical errors and provability of these failures result in the complication of producing efficient legal guarantees for protection of the patient`s right. The peculiarity of this medical and legal substrate is that it synthesizes the awareness of rights and medicine both through the lens of their achievements. A clear vision of such a phenomenon as medical malpractice (error) has a priori significance for the legal environment. It is a sparkling example of the epistemological and gnoseological interaction of the medical and legal knowledge as to determine criteria of medical malpractices is to set “boundaries” of the legal regulation. Here we mean the occurrence of legal consequences in committing an error of law. Conclusions. For a more complete understanding of cases of legal consequences the following regulatory measures of prevention of medical malpractice cases are necessary: establishment of an effective system of prudential internal control of defects in the medical care; specialised training for medical personnel on methods of detection of medical malpractices, their prediction and prompt elimination of possible consequences; instrumental, functional and system-structural measures for reducing risks of medical malpractice, namely: actions for reducing medical errors caused by system determinants (failures, disorders, etc.), actions for reducing medical errors made in prescribing and applying medicaments, medical errors happened because of the medical intervention, surgical in particular; improvement of the legal support of guarantees of patients and doctors rights for a safe delivery of medical aid and prevention of medical errors.

Робота присвячена визначенню підстав для настання правових наслідків при здійсненні лікарської помилки. Мета роботи – встановлення основних ознак «лікарської помилки» в медико-правовому аспекті, а також класифікація організаційно-правових заходів превенції лікарських помилок і редукування цих проблем. Методи. Комплексно-критичний, семіотичний, синергетичний, антропологічний, герменевтичний, порівняльно-правовий і метод нормативного порівняння. Результати. Визначення наявності лікарської помилки ускладнюється її поняттєво-термінологічною константою. Адже принципові відмінності в інтерпретації, розумінні, кваліфікації, встановленні дефектів, лікарських помилок і доведенні цих помилок призводить до ускладнення вироблення ефективних правових гарантій захисту прав і пацієнтів, і лікарів. Особливість цього медико-правового субстрату – він синтезує в собі знання як про право, так і про медицину через призму їх досягнень. Чітке уявлення про таке явище, як лікарська помилка має апріорне значення для правового поля. Це яскравий приклад гносеологічної та епістемологічної взаємодії медичних і правових знань. Адже визначення критеріїв медичної помилки є визначенням «меж» правового регулювання, тобто настання правових наслідків при здійсненні правової помилки. Висновки. Для превенції та правильного кваліфікування правових наслідків лікарських помилок необхідні організаційно-правові заходи: удосконалення системи пруденційного внутрішнього контролю дефектів медичної допомоги; спеціалізована підготовка медперсоналу за технологією виявлення лікарських помилок, їх прогнозування та оперативного усунення можливих наслідків; заходи інструментальної, функціональної та системно-структурної спрямованості зі зниження ризиків скоєння лікарських помилок, а також їх редукування; удосконалення правового забезпечення гарантій прав пацієнтів і лікаря на безпечне й ефективне надання медичної допомоги.

Работа посвящена определению оснований для наступления правовых последствий при совершении врачебной ошибки. Цель работы – определение основных признаков «врачебной ошибки» в медико-правовом срезе, а также классификация организационно-правовых мер превенции врачебных ошибок и редуцирования этих проблем. Методы. Комплексно-критический, семиотический, синергетический, антропологический и герменевтический, сравнительно-правовой, метод нормативного сравнения. Результаты. Определение наличия допущенной врачебной ошибки усложняется ее понятийно-терминологической константой. Принципиально существенные отличия в интерпретации, понимании, квалификации, установлении дефектов, врачебных ошибок и доказуемости этих ошибок усложняет выработку эффективных правовых гарантий защиты прав и пациентов, и врачей. Особенность этого медико-правового субстрата – он синтезирует в себе знание как о праве, так и о медицине через призму их достижений. Четкое представление о таком явлении, как врачебная ошибка имеет априорное значение для правового поля. Это яркий пример гносеологического и эпистемологического взаимодействия медицинских и правовых знаний. Определение критериев медицинской ошибки является определением «границ» правового регулирования, т. е. наступлением правовых последствий при совершении правовой ошибки. Выводы. Для превенции и правильной квалификации правовых последствий врачебных ошибок необходимы организационно-правовые меры: усовершенствование системы пруденциального внутреннего контроля дефектов медицинской помощи; специализированная подготовка медперсонала по технологии выявления врачебных ошибок, их прогнозирования и оперативного устранения возможных последствий; меры инструментальной, функциональной и системно-структурной направленности по снижению рисков совершения врачебных ошибок и по редуцированию врачебных ошибок; усовершенствование правового обеспечения гарантий прав пациентов и врача на безопасное и эффективное оказание медицинской помощи.
Yanchuk A. O. Legal consequences, measures of prevention and reduction of medical malpractice cases (errors) / A. O. Yanchuk, A. O. Zaporozhchenko, I. P. Katerynchuk, S. O. Kuznichenko, O. V. Kryzhanovska // Pathologia. - № 1. - Zaporozhye State medical university, 2019. – P. 124-130.
Keywords: medical errors; health care; legal liability; лікарська помилка; медична допомога; цивільно-правова відповідальність; врачебная ошибка; медицинская помощь; гражданско-правовая ответственность; Research Subject Categories::LAW/JURISPRUDENCE